Prevalence, incidence density, and genotype distribution of GB virus C infection in a cohort of recently HIV-1-infected subjects in Sao Paulo, Brazil. - Maria Teresa M Giret (Public Library of Science (PLoS), 2011)
Background The results of previous studies elsewhere have indicated that GB virus C (GBV-C) infection is frequent in patients infected with the human immunodeficiency virus type 1 (HIV-1) due to similar transmission routes of both viruses. The aim of this study was to determine the prevalence, incidence density and genotypic characteristics of GBV-C in this population. Methodology/principal findings The study population included 233 patients from a cohort primarily comprised of homosexual men recently infected with HIV-1 in São Paulo, Brazil. The presence of GBV-C RNA was determined in plasma samples by reverse transcriptase-nested polymerase chain reaction and quantified by real-time PCR. GBV-C genotypes were determined by direct sequencing. HIV viral load, CD4+ T lymphocyte and CD8+ T lymphocyte count were also tested in all patients. The overall prevalence of GBV-C infection was 0.23 (95% CI: 0.18 to 0.29) in the study group. There was no significant difference between patients with and without GBV-C infection and Glycoprotein E2 antibody presence regarding age, sex, HIV-1 viral load, CD4+ and CD8+T cell counts and treatment with antiretroviral drugs. An inverse correlation was observed between GBV-C and HIV-1 loads at enrollment and after one year. Also, a positive but not significant correlation was observed between GBV-C load and CD4+ T lymphocyte. Phylogenetic analysis of the GBV-C isolates revealed the presence of genotype 1 and genotype 2, these sub classified into subtype 2a and 2b. Conclusion/significance GBV-C infection is common in recently HIV -1 infected patients in Sao Paulo, Brazil and the predominant genotype is 2b. This study provides the first report of the GBV-C prevalence at the time of diagnosis of HIV-1 and the incidence density of GBV-C infection in one year.